Attack Intention Recognition: A Review - Ahmed, Abdulghani Ali; Noorul Ahlami, Kamarul Zaman (IJNS, 2017)
Sensitive information faces critical risks when it is transmitted through computer networks. Existing protection systems are still limited in their capacities to ensure network information has sufficient confidentiality, integrity, and availability. The rapid development in network technologies has only helped increase network attacks and hide their malicious intent. This paper analyzes attack types and classifies them according to their intent. A causal network approach is used to recognize attackers’ plans and predict their intentions. Attack intention is the ultimate attack goal which the attacker attempts to achieve by executing various methods or techniques, and recognizing it will help security administrators select an appropriate protection system.